Apoptosis resistance induced by cytokines in SW 982 culture was suppressed by red jasmine rice (Oryza sativa Linn.) crude extract - Ongchai, Siriwan; Jaitham, Rungnaree; Thonghoi, Supitcha; Kongdang, Patiwat; Yodkeeree, Supachai; Limtrakul, Pornngarm (Biomedical Sciences and Clinical Medicine, 2018)
Background Rhuematoid arthritis (RA) is associated with inflammation of the synovial membrane which results in an abnormal proliferation and resistance to the apoptosis process in synovial fibroblasts leading to synovial hyperplasia and joint destruction. Reversal of apoptosis resistance of fibroblasts in RA synovium is one of the targets for suppression of RA pathogenesis. Objectives This study aimed to investigate the apoptosis-inducing effects of crude extract of red jasmine rice (CE) on proinflammatory cytokine-stimulated apoptosis resistance in a human synovial sarcoma cell line (SW982). Methods SW982 cells were preincubated for 6 hours with combined cytokines, tumor necrosis factor-α (TNF-α), and interleukin 17-A (IL-17A). That was followed by the addition of CE at a concentration of 12.50-100 µg/ml. After either 24 or 48 hours of incubation, expression of apoptotic related genes, including the FLICE-like inhibitory protein gene (FLIP), the anti-apoptotic gene (Bcl-2), and the pro-apoptotic gene (Bax), was determined by real-time PCR. Expression of the apoptotic cells was determined by flow cytometric analysis and the caspase-3 activity was analyzed by ELISA. Results The expression of the apoptosis resistance markers, FLIP and Bcl-2/Bax ratio, was significantly elevated when the cells were treated with the combined cytokines compared with the control group. These markers were significantly decreased when co-treated with CE. These results were concomitant with a rise in caspase-3 activity and an increase in apoptotic cells when compared to the cytokine-treated group. Conclusions CE reduces cytokine-induced apoptotic resistance in SW982 cells via down regulation of the expression of anti-apoptotic genes. These results suggest application of CE is an alternative treatment of RA.